3(x-8)=9x

Simple and best practice solution for 3(x-8)=9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-8)=9x equation:


Simplifying
3(x + -8) = 9x

Reorder the terms:
3(-8 + x) = 9x
(-8 * 3 + x * 3) = 9x
(-24 + 3x) = 9x

Solving
-24 + 3x = 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-24 + 3x + -9x = 9x + -9x

Combine like terms: 3x + -9x = -6x
-24 + -6x = 9x + -9x

Combine like terms: 9x + -9x = 0
-24 + -6x = 0

Add '24' to each side of the equation.
-24 + 24 + -6x = 0 + 24

Combine like terms: -24 + 24 = 0
0 + -6x = 0 + 24
-6x = 0 + 24

Combine like terms: 0 + 24 = 24
-6x = 24

Divide each side by '-6'.
x = -4

Simplifying
x = -4

See similar equations:

| 3x+9-2x=13 | | 4x^4-20x^2+16=0 | | 26x+12=5(5x+4) | | 10-(2*-4)+3x=16 | | (5u+3)(5-u)=0 | | 3x+9-2x=14 | | 2x-6x+9=x-6+15 | | (7x^2+5x)/(x^2+1)-5x/(x^2-6) | | 5w+2.7=12 | | 9x^2+169=0 | | 3x+9x-4=3(4x+9) | | -8=-(-6x-3) | | .5x-4=0 | | 2y+2(y-6)=8y-6(y-10) | | 9(x-1)=-126 | | 7/36*x=5 | | 4(x-2)=2x-2 | | 52=p-41 | | -(8x-4)-(3x-5)+10=-9(x-1)-(5x+8+3) | | 7x-2+5=10x+4 | | p+13=-10 | | 6x+9-5x=16 | | -2(3x-6)+5=-1 | | 8y=5y+9 | | Rx+Sy=Tfory | | (-5+7i)+(-8-9i)=0 | | (x)=3x+4 | | x-9/5-1=x-3/4 | | 5x-11=4x+6 | | 4w-6w=12 | | 9x-15=6x | | X-3/4(2x-12)=7x/2+5 |

Equations solver categories